Perilaku Konsumen pada keputusan pembelian minyak goreng kemasan - Yuliana, Revi; Andriani, Evi; Nurmalia, Ana (SINTA Journal (Science, Technology, and Agricultural), 2024)
Cooking oil is consumed by almost all people, both at the household level and in the food industry. The level of purchase of packaged cooking oil can be influenced by various factors, including consumer preferences, price, promotions, product quality and market trends. This research aims to determine the level of purchasing packaged cooking oil in Bengkulu City and the decision to purchase packaged cooking oil. This research was carried out purposively. This research is quantitative and uses the SPSS application. The research locations at BIM, Pasar Panorama, Pasar Minggu, Indomaret, and Alfamart were deliberately chosen because they have the highest population in Bengkulu City. The results of my research show that the highest level of purchasing packaged cooking oil is at the 2 liter level, namely 51 respondents and the percentage value is (50.49) while the lowest is at the 5 liter level with 2 respondents and the percentage value is (1.92) and the average The score was 2.14 (Low) with a total of 96 respondents. To understand how to increase purchases of packaged cooking oil, it is necessary to conduct market and trend research. The results of multiple linear regression analysis show independent variables, variable (X1). Kita oil price (X2) Komplementer (X3), net family income (Na) Number of family member (X4) The results of multiple linear regression analysis show the independent variables (variable X5 ) Healthy living motivation (X6) together influences the dependent variable (variable Y) purchasing decisions.